Pengaruh Kualitas Pelayanan dan Kompetensi Fiskus Terhadap Kepuasan Wajib Pajak - Sitti Mispa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2018)
The purpose of the research were : 1) to analyze the influence mix marketing consisted product, price, promotion and location toward the satisfaction of customer at PT. Belian Cahya Utama in Makassar and 2) identify the most dominant variable in influencing toward the satisfaction of customer at PT. Belian cahya Utama in Makassar. The populations of the research were 117 customers of Housing Permata Indah Regency and Griya Bandara Permai in Makassar. Total sample were 90 customers. The research used primary data and secondary data. Method of analysis data used descriptive statistic analysis and multiple linear regressions using SPSS program. The result of the research showed that the variable product, price, promotion, and location gave the positive influence significantly toward the satisfaction of the customers at PT. Belian Cahya Utama in Makassar. Further, in partially, the research showed that the variable product, price, and location had the positive influence in satisfaction of customer while the variable of promotion did not. Moreover, the variable of product was the most dominant influence in satisfaction of customers.